M=( 3+x/x-3 + 18/9-x^2 + x-3/x+3 ) : ( 1 – x+1/x+3 )

Question

M=( 3+x/x-3 + 18/9-x^2 + x-3/x+3 ) : ( 1 – x+1/x+3 )

in progress 0
Melanie 1 năm 2021-09-12T00:00:27+00:00 2 Answers 9 views 0

Answers ( )

    0
    2021-09-12T00:01:50+00:00

    Đáp án + giải thích bước giải :

    `M = ( (3 + x)/(x – 3) + 18/(9 – x^2) + (x – 3)/(x + 3) ) : (1 – (x + 1)/(x + 3) )` 

    `⇔ M = ( (x^2 + 6x + 9)/(x^2 – 9) – 18/(x^2 – 9) + (x^2 – 6x + 9)/(x^2 – 9) ) . (x^2 – 9)/(2 (x – 3) )`

    `⇔ M = ( (x^2 + 6x + 9 – 18 + x^2 – 6x + 9)/(x^2 – 9) ) . (x^2-9)/(2 (x – 3) )`

    `⇔ M = ( ( (x^2 + x^2) + (6x – 6x) + (9 + 9 – 18) )/(x^2 – 9) ) . (x^2 – 9)/(2 (x – 3) )`

    `⇔ M = (2x^2)/(x^2 – 9) . (x^2 – 9)/(2 (x – 3)`

    `⇔ M = x^2/(x – 3)`

    0
    2021-09-12T00:01:58+00:00

    `M = ( (3+x)/(x-3) – 18/(9-x^2) + (x-3)/(x+3) ) : ( 1 – (x+1)/(x+3) )`

    `⇒ M = ( ((x+3)^2)/(x^2-9) – 18/(9-x^2) + ((x-3)^2)/(x^2-9) ) : 2/(x+3)`

    `⇒ M = ((x^2+6x+9-18+x^2-6x+9)/(x^2-9) ) xx ((x^2-9)/(2.(x-3)))`

    `⇒ M = (2x^2)/(x^2-9) xx (x^2-9)/(2.(x-3))`

    `⇒ M = (x^2)/(x-3)`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )